ANALISIS KEBUTUHAN PENGEMBANGAN BUKU CERITA BERGAMBAR BERBASIS KETERAMPILAN MENULIS TEGAK BERSAMBUNG DALAM PEMBELAJARAN BAHASA INDONESIA KELAS III SD - Vera Juniar; Anggi Citra Apriliana; Edwita, Edwita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the need for developing illustrated storybooks based on cursive writing skills in Indonesian language learning for third-grade elementary school students. The study used a qualitative descriptive approach through observation, interviews with teacher, and questionnaires for students. The results showed that students still experience difficulties in cursive writing, while classroom learning is still dominated by the use of textbooks, resulting in a lack of variety. In addition, all students require engaging learning media and prefer learning that involves stories, games, pictures, and videos. Therefore, the development of illustrated storybooks that use contextual stories, engaging illustrations, and gradual writing activities is expected to help students improve their cursive writing skills according to their developmental characteristics.